Effects of Purple-Fleshed Sweet Potato Lyophilized Powder on the Physicochemical Properties, Lactic Acid Bacteria Viability, Microstructure, and Textural Properties of Stirred Yogurt - Paulo Cezar da Cunha Júnior; Carlos Alberto Cruz Pinto; Jorge Manuel Alexandre Saraiva; Elisa Helena da Rocha Ferreira (Foods)
This study proposes the use of lyophilized powder of purple-fleshed sweet potato (LP) as a new multifunctional ingredient to improve the identity and quality parameters of stirred yogurts. The physical and chemical properties, color, monomeric anthocyanin content, lactic acid bacteria viability, water retention capacity, microstructure, and texture were evaluated for yogurts enriched with LP at the levels of 2% (YLP2), 4% (YLP4), and 6% (YPL6), stored for 30 days under refrigeration (4 °C). The results indicated that LP provided different intensities and shades of pink coloration to yogurt, in addition to increasing (p < 0.05) the water retention capacity and reducing the water activity. No post-acidification processes were observed during storage. YLP2, YLP4, and YLP6 showed higher stability regarding the number of viable lactic acid bacteria cells compared to the control sample (without enrichment) during storage. Interstitially, adding LP improved the microstructures of the yogurts, promoting more cross-linked networks, with greater uniformity and smaller empty zones, regardless of the level used; in addition, the yogurts (YLP4 and YLP6) were firmer and creamier. These findings demonstrate that LP can be used as a multifunctional ingredient to promote technological/functional improvements, being underscored as a promising natural colorant, stabilizer, emulsifier, and thickener for yogurts.